The positive implication of natural antioxidants on oxidative stress-mediated diabetes mellitus complications - Shouvik Mallik; Bijoy Paria; Sayed Mohammad Firdous; Hesham S. Ghazzawy; Nashi K. Alqahtani; Yong He; Xiaoli Li; Mostafa M. Gouda (Journal of Genetic Engineering and Biotechnology)
The complementary intervention to modulate diabetes mellitus (DM) metabolism has recently brought the global attention, since DM has become among the global burden diseases. Where, several related pathways elevate the production of superoxide in consequences. For example, the flux of glycation-derived end products (AGEs) could lead to the deactivation of insulin signaling pathways. In that context, many vitamins and phytochemicals in natural sources have high antioxidant impacts that reduce oxidative stress and cell damages. These chemicals could be applied as bioactive antidiabetic agents. Their mode of actions could be from regulating the intracellular reactive oxygen species (ROS) which cause several pro-inflammatory pathways related to the oxidative stress (OS) and DM. Besides, they have a great potential to control the epigenetic mutations and hyperglycemia and help in back the blood glucose to the normal level. Therefore, the current review addresses the important role of natural functional antioxidants in DM management and its association with its OS complications.